Communities and Conservation: Marula Trees (Sclerocarya birrea subsp. caffra) Under Communal Management at Matiyane Village, Limpopo Province, South Africa. (February 2019) - Sinthumule, Ndidzulafhi Innocent; Mzamani, Leonard Colbert Mbhoni
Sclerocarya birrea subsp. caffra (Marula) is widely used throughout its natural distribution range by rural populations to meet livelihoods requirements. Every part of the tree, including the fruits, branches, stem and roots, provides goods and services of high cultural, social, and economic importance. Its usefulness and unique properties have encouraged local people to retain S. birrea in communal areas. However, there is a paucity of data quantifying the role of local communities in conserving S. birrea . This study quantifies the role of local communities in protecting S. birrea in 300 randomly selected households in Matiyane Village, Limpopo Province, South Africa. The study found that the majority of the respondents (92%; N = 276) are positive about the conservation of S. birrea. Most importantly, the respondents play a significant role in the protection of S. birrea in the village. Management strategies and factors responsible for the protection of S. birrea in communal land are discussed.